Absence of shock therapy related to improper sensing of noise on the defibrillation test during subcutaneous implantable cardioverter–defibrillator implantation: a case report. Issue 6 (2nd December 2020) - Tamura, Shota; Yoshiyama, Tomotaka; Doi, Atsushi; Yoshiyama, Minoru
Abstract: Background : Subcutaneous implantable cardioverter–defibrillator (S-ICD) represents an efficient alternative to transvenous ICD in patients who do not require pacing. The intraoperative defibrillation test (DFT) is recommended during S-ICD implantation to confirm appropriate sensing and successful 65-J termination of induced ventricular fibrillation (VF). However, few cases of oversensing of noise inhibiting therapies have been reported. Case summary : We report the case of a 50-year-old man who underwent S-ICD implantation for secondary prevention of sudden cardiac death. Immediately after S-ICD implantation, VF was induced using a 50-Hz burst; however, shock was not delivered owing to sustained noise on the electrogram in the primary vector. Therefore, an external rescue shock was needed at 150 J. We changed the sensing vector from primary to secondary and performed a second DFT. The S-ICD could deliver an appropriate shock and was able to successfully terminate VF without noise markers in the secondary vector. During the second DFT, one back-up pacing was delivered after the shock; the sensing vector then automatically switched from the secondary to the alternate vector. However, noise was observed in the alternate vector despite sinus rhythm restoration. Discussion : The present case demonstrated that noise was recorded in two different vectors during DFT, possibly supporting the hypothesis that the muscle spasm of the diaphragm induced by the 50-Hz burst causes oversensing of noise by the S-ICD.